Analisis Daya Tarik Industri BMT: Studi Pada Industri BMT Di Kota Metro Lampung - Rosid, Andiana; Imantoro, Jati (Jurnal Manajemen Magister Darmajaya, 2018)
This study aims to describe the Baitul Maal Wattamwil (BMT) industrial attractiveness in the city of Metro Lampung. For this purpose, this study uses a multiple case study approach on 10 BMTs in Metro Lampung. Data collection was conducted by in-depth interviews and supported by the Industrial Attractiveness Matrix (MDTI) as an analytical tool. The results showed several factors that are considered important for industrial attractiveness. Those are (in order): the profitability of the industry, the competition structure, and industry cycle. While some of the decisive factors of business strength for the BMT industry are (in order): the company's image, cash flow, and product / service quality. The results of the analysis showed that generally, the industrial attractiveness of BMT in Metro city is in the phase of decreasing. The main factor which causes this condition is the decreasing of the public trust, which is caused by the growth failure from many BMTs in Metro. It is also followed by the emergence of substitute products named micro financing from industrial banking with lower rate interest compared to BMT products. A unique finding in this study is that the legal factors are not considered as the industrial support (NO GO). It is because the law supervision in BMT is not strict enough, which makes the establishment for new BMTs is become easier. Ultimately, many BMTs are failed to grow (bankrupt) or related to customer fund fraud cases. These conditions have an impact on the decreasing level of consumer trust. Finally, the corporate image is a key to success and to survive in this industry. The preferred strategies in this condition are a selective growth and wait for an improvement of the industrial conditions.Keywords — The Industrial Attractiveness Matrix (MDTI), Baitul Mall Wattamwil (BMT).